2018
DOI: 10.22391/fppc.401101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mean platelet volume and platelet count in patients with schizophrenia

Abstract: Introduction: Compared to the general population, cardiovascular diseases are more common in schizophrenia patients and the mortality rate is higher than the general population. One of the explanations for increased cardiovascular events in patients with schizophrenia is the increase in platelet activity. Platelets are essential for progression of atherosclerotic lesions, plaque destabilization, and thrombus formation. Mean platelet volume (MPV) is a measure of platelet size and a good marker of platelet funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Another study described an increase in MPV in patients with schizophrenia on treatment with typical or atypical antipsychotics compared to a control group the same study assessed platelet counts in both groups and identified a decreased value in the schizophrenia group compared to the healthy group. In addition, the schizophrenia group had a higher body mass index than the control group, which could be related to the increase in MPV ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study described an increase in MPV in patients with schizophrenia on treatment with typical or atypical antipsychotics compared to a control group the same study assessed platelet counts in both groups and identified a decreased value in the schizophrenia group compared to the healthy group. In addition, the schizophrenia group had a higher body mass index than the control group, which could be related to the increase in MPV ( 11 ).…”
Section: Introductionmentioning
confidence: 99%